Standardization of grafting of mango as affected by method, time and rootstocks age under Tripura condition - Das, Biswajit; Devi, H. Lembisana; Kandpal, B. K. (Indian Journal of Hill Farming, 2019)
The present study was carried out to standardize the epicotyl and softwood grafting techniques under Tripura condition considering the availability time of mango stones, suitable grafting time, appropriate rootstock age and grafting height. Epicotyl grafting was highly successful on 10 to 20 days old rootstocks during 1st June to 1st August with average graft success of 81.9%-85.1%. In the first year, softwood grafting can be done on 3 months (1st September) to 3½ months (15th September) old rootstocks at 8-10 cm height (79.5%-80.5% graft success). In the second year, softwood grafting is highly successful on 10 months (1st April) to 12 months (1st June) old rootstocks at 12-14 cm height (73.35-86.9% graft success), on 10 months (1st April) to 15 months (1st September) old rootstocks at 16- 18 cm height (75.7%-91.3% graft success) and on 12 months (1st June) to 15 months (1st  September) old rootstocks at 20-24 cm height (76.5%-88.3%). Further, during October to February is not suitable time for mango grafting as low temperature and low relativehumidity prevails during this period under Tripura Condition.